Description of Coiffaitarctia imperatrix sp. nov. (Lepidoptera: Erebidae: Arctiini) from Peruvian Amazon - Grados, Juan (2014)
The adult male and its genitalia are described and illustrated for Coiffaitarctia imperatrix, new species of Phaegopterina (Arctiini) found in the Peruvian Amazon.